City at the foot of Bakony Mountains - Hornyák, Attila (4D Journal of Landscape Architecture and Garden Art, 2010)
The plans for the Agora Square and the Torna-creek rehabilitation have been prepared by Üzenet Ltd. and Stúdió 73 Ltd. with the directions of Koszorú Lajos and Mohácsi Sándor. As a result of the Torna-creek rehabilitation, the area will be an integrated part of the city center, with the possibility of extension of the commercial units towards the creek. The competition site and the functional program of Europan 10 is also part of the development concept of the center. It addresses one specific problem in the area, which is awaiting refurbishment and rehabilitation. In previous years, the city has devoted its resources to the high-quality renewal of its public spaces and public institutions. The open-air swimming pool of the city has been refurbished and five new open-air pools with 1700 m2 surface area have been added to it.